1975
DOI: 10.1021/jm00244a003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of nucleoside transport. Structure-activity study using human erythrocytes

Abstract: The passage of nucleosides across the plasma membrane of erythrocytes is a membrane-mediated process which is strongly inhibited by derivatives of 9-beta-D-ribofuranosylpurine (1) with S, O, or N atoms at the purine 6 position bearing variously substituted arylalkyl groups. In this structure-activity study, nucleoside derivatives were compared in respect to their ability to inhibit a transport-dependent aspect of nucleoside metabolism in erythrocytes, the synthesis of inosine from external guanosine and hypoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 10 publications
1
47
0
Order By: Relevance
“…Crystals were collected after 20 h, and were subsequently washed with ether and petroleum ether and kept desiccated in vacuo at 4°C. The properties of the final products (IR, UV and visible spectra, melting points, and chromatography properties) are essentially similar to those published in a recent work (11).…”
Section: Chemicalssupporting
confidence: 79%
“…Crystals were collected after 20 h, and were subsequently washed with ether and petroleum ether and kept desiccated in vacuo at 4°C. The properties of the final products (IR, UV and visible spectra, melting points, and chromatography properties) are essentially similar to those published in a recent work (11).…”
Section: Chemicalssupporting
confidence: 79%
“…The training set used for developing 3D-QSAR models included 77 compounds and comprised a series of compounds with a high diversity in structure and a wide range of ENT1 inhibitory potencies as reported by Paul et al, 28 a series of tetrahydroisoquinoline conformationally constrained ENT1 inhibitors reported by us, 1 and a series of 5′-O, 8-cyclo conformationally constrained ENT1 inhibitors, reported in this study (see Table 1). The test set included 39 compounds with biological data taken from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The differences emphasize the remarkable regioselectivity of ENT1 among these tetrahydroisoquinoline NBMPR analogues with respect to the NO 2 substituent. 28,34 Compared to their less constrained counterparts compounds 2-5, the binding affinities of compounds 6-9 were significantly lower (see Table 4, K i values increased from the nanomolar range to the micromolar range except for compound 8). These results are interesting since compounds 6-9 were obtained by just forming a 5′-O, 8-linkage to block the free rotation of the N 9 -C 1′ glycosidic bond in compounds 2-5, respectively.…”
Section: Ent1 Inhibitory Activity Of Novel 5′-o 8-linkage Constrainementioning
confidence: 96%
See 1 more Smart Citation
“…It is noteworthy that the amino acid sequence between residues 99 and 231 is highly conserved between species (Figure 2), suggesting that differences in dipyridamole sensitivity may be due to discrete amino acid substitutions in this region. Structure-activity studies [19,34,38] have led to the hypothesis that interactions with discrete hydrophobic elements of the transporter are required for high-affinity binding of inhibitors to hENT1. Comparative hydropathy analysis showed that residues 50-67 of the first extracellular loop of hENT1 are significantly more hydrophobic than the corresponding residues in mENT1 and rENT1 ; indeed, this region is the only one that displays a marked difference in hydrophobicity among the species examined.…”
Section: Ment1mentioning
confidence: 99%